Exercise descriptors that determine muscle strength gains are missing from reported anterior cruciate ligament reconstruction rehabilitation programs: A scoping review of 117 exercises in 41 studies - Vlok, A.; van Dyk, N.; Coetzee, D.; Grindem, H. (Journal of Orthopaedic & Sports Physical Therapy, 2022)
Objectives: (1) Describe which strength training exercise descriptors are reported in anterior cruciate ligament reconstruction (ACLR) rehabilitation research and (2) compare the current standards of reporting ACLR strength training exercise descriptors to international best practice strength training guidelines. Design: Scoping review. Literature Search: We searched the Medline, PsycINFO, CINAHL, SPORTDiscus, Academic Search, ERIC, Health Source Nursing, Health Source Consumer, MasterFILE, and African Wide Information databases. Study Selection Criteria: We included level I-IV studies of ACLR rehabilitation programs with one or more reported strength training exercise descriptor. We used a predefined list of 19 exercise descriptors based on the American College of Sports Medicine (ACSM) exercise recommendations, the Consensus on Exercise Reporting Template (CERT), and Toigo and Boutelliers` exercise descriptor framework. Data Synthesis: Completeness and standard of reporting exercise descriptors in ACLR rehabilitation programs were assessed by means of best practice strength training international standards. Results: We extracted data on 117 exercises from 41 studies. A median of 7 of the 19 possible exercise descriptors were reported (range 3-16). Reporting of specific exercise descriptors varied across studies from 93% (name of the strength training exercise) to 5% (exercise aim). On average, 46%, 35%, and 43% of the exercise descriptors included in the ACSM, CERT, and Toigo and Boutellier guidelines were reported, respectively. Conclusion: Key exercise descriptors for muscle strength gains are not reported in studies on ACLR rehabilitation. Only the exercise name, number of exercises and the experimental period were reported in most of the studies.